Preoperative evaluation of vascular morphology and function of living renal donors on multi-detector row CT - Duong Phuoc Hung; Le Trong Khoan, Nguyen Khoa Hung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objectives: The study aims to evaluate the vascular morphology and function of living renal donors using Multi-Detector CT (MDCT). Material and Methods: From January 2017 to August 2018, a cross-sectional study was conducted at the Cardiovascular Centre of Hue Central Hospital. We performed 64-MDCT with unenhanced and three enhanced CT scans (arterial, parenchymal, and secretory phases) along with two additional dynamic scans. The study included 154 living renal donors who underwent nephrectomy. Renal vascular morphology was compared with operational findings, and renal function was calculated using the Patlak equation and compared with single photon emission computed tomography (SPECT). Results: Among the 154 living renal donors (male/female: 83.77%/16.23%), the mean age was 30.72 ± 8.21 years (range: 20-60 years). The kidneys chosen for nephrectomy included 49.35% right and 50.65% left kidneys. Variations in arteries and veins were noted. CT findings corresponded with operational findings, achieving 100% sensitivity, positive predictive value, specificity, and negative predictive value. All living donors exhibited normal renal function in the excretory phase at 5 minutes post-contrast injection. The GFR calculated from CT positively correlated with the GFR from SPECT. Conclusions: MDCT not only provides accurate diagnosis of vascular morphology but also facilitates the calculation of renal function in living renal donors, aiding surgeons in planning appropriate operations for selected kidneys.